Self-control in Online Discussions: Disinhibited Online Behavior as a Failure to Recognize Social Cues - Voggeser, Birgit J.; Singh, Ranjit K.; Göritz, Anja S. (Frontiers in Psychology, 2018)
In an online experiment we examined the role of self-control in recognizing social cues in the context of disinhibited online behavior (e.g., flaming and trolling). We temporarily lowered participants' self-control capacity with an ego depletion paradigm (i.e., color Stroop task). Next, we measured participants' sensitivity to social cues with an emotional Stroop task containing neutral, negative, and taboo words. Sensitivity to social cues is represented by the increase in reaction time to negative and especially taboo words compared to neutral words. As expected, undepleted participants were slower to process the color of negative and taboo words. By contrast, depleted participants (i.e., those with lowered self-control capacity) did not react differently to taboo or negative words than they did to neutral words. The experiment illustrates that self-control failure may manifest itself in a failure to recognize social cues. The finding underlines the importance of self-control in understanding disinhibited online behavior: Many instances of disinhibited online behavior may occur not because people are unable to control themselves, but because they do not realize that a situation calls for self-control in the first place.